The Hyperpolarization-Activated Current Determines Synaptic Excitability, Calcium Activity and Specific Viability of Substantia Nigra Dopaminergic Neurons - Carbone, Carmen; Costa, Alessia; Provensi, Gustavo; Mannaioni, Guido; Masi, Alessio (Frontiers in Cellular Neuroscience, 2017)
Differential vulnerability between Substantia Nigra pars compacta (SNpc) and Ventral Tegmental Area (VTA) DAergic neurons is a hallmark of Parkinson’s Disease (PD). Understanding the molecular bases of this key histopathological aspect would foster the development of much-needed disease-modifying therapies. Non-heterogeneous DAergic degeneration is present in both toxin-based and genetic animal models, suggesting that cellular specificity, rather than causing factors, constitutes the background for differential vulnerability. In this regard, we previously demonstrated that MPP+, a neurotoxin able to cause selective nigrostriatal degeneration in animal rodents and primates, inhibits the Hyperpolarization-activated current (Ih) in SNpc DAergic neurons and that pharmacological Ih antagonism causes potentiation of evoked Excitatory Post-Synaptic Potentials (EPSPs). Of note, the magnitude of such potentiation is greater in the SNpc subfield, consistent with higher Ih density. In the present work, we show that Ih block-induced synaptic potentiation leads to the amplification of somatic calcium responses (SCRs) in vitro. This effect is specific for the SNpc subfield and largely mediated by L-Type calcium channels, as indicated by sensitivity to the CaV 1 blocker isradipine. Furthermore, Ih is downregulated by low intracellular ATP and determines the efficacy of GABAergic inhibition in SNpc DAergic neurons. Finally, we show that stereotaxic administration of Ih blockers causes SNpc-specific neurodegeneration and hemiparkinsonian motor phenotype in rats. During PD progression, Ih downregulation may result from mitochondrial dysfunction and, in concert with PD-related disinhibition of excitatory inputs, determine a SNpc-specific disease pathway.